PENGARUH PEMBERIAN KOMPOS AMPAS KELAPA TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea robusta L.) PADA MEDIA PODSOLIK MERAH KUNING - prihatin ningsih, siska; Sopiana, Sopiana; Nurhayati, Nurhayati (Journal of Agro Plantation (JAP), 2023)
The use of red-yellow podzolic media for coffee seedlings still needs to be considered because red-yellow podzolic soils still have problems such as low soil pH and low nutrient content. One alternative to using organic fertilizers and inorganic fertilizers is coconut pulp which contains 0.92% N, 0.17% P, and 0.25% K. This study aims to determine the effect of coconut compost on the growth of robusta coffee seedlings on red yellow podzolic media. The study was carried out at the Ketapang State Polytechnic Experimental Garden, from September to December 2021. The study used a completely randomized design (CRD) consisting of 5 treatments and 5 treatments. replications, so that there are 25 experimental units, each experimental unit consists of 3 samples so that the total number is 75 samples. The treatments are K0: No Composted Coconut Dregs, K1: 150 g/polybag, K2: 200 g/polybag, K3: 250 g/polybag, K4: 300 g/polybag. Parameters observed were plant height, stem diameter, number of leaves, leaf length, leaf width, and plant weight. Based on the results of further tests, presenting coconut pulp compost had a significant effect on plant height, stem diameter, number of leaves, leaf length, leaf width, and plant dry weight with K4 treatment (coconut pulp compost 300 g/polybag).